1998
DOI: 10.1038/sj.bmt.1701118
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation in chronic myeloid leukaemia using Philadelphia chromosome negative blood progenitors mobilised with hydroxyurea and G-CSF

Abstract: Summary:Autologous transplantation in CML has been a focus of interest over the last few years. Determining the indications, optimal timing and method for this procedure remains controversial. One approach has been the mobilisation of Philadelphia chromosome negative (Ph؊) peripheral blood stem cells following high-dose chemotherapy as a method of purging the graft. We have described a mobilisation regimen of 7 days of hydroxyurea followed by G-CSF and have shown it to be substantially less toxic than other me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Following initial studies which showed that autografting CML patients with re-infusion of chronic phase cells after transformation of the disease to an acute phase was successful in re-establishing a chronic phase, 4,5 it became evident from several studies that autografting in chronic phase may induce a sustained period of Phnegative hematopoiesis in patients who received PBPC obtained after chemotherapy. 9,13,18,21,26,28 Although these studies have provided interesting information from a biological point of view and have suggested a potential role for chemotherapy in the management of CML patients, the selection of patients and the heterogeneity of treatments received and purging procedures have limited the evaluation of the clinical responses of autografting in disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following initial studies which showed that autografting CML patients with re-infusion of chronic phase cells after transformation of the disease to an acute phase was successful in re-establishing a chronic phase, 4,5 it became evident from several studies that autografting in chronic phase may induce a sustained period of Phnegative hematopoiesis in patients who received PBPC obtained after chemotherapy. 9,13,18,21,26,28 Although these studies have provided interesting information from a biological point of view and have suggested a potential role for chemotherapy in the management of CML patients, the selection of patients and the heterogeneity of treatments received and purging procedures have limited the evaluation of the clinical responses of autografting in disease.…”
Section: Discussionmentioning
confidence: 99%
“…All products of leukapheresis obtained from available patients enrolled in the study were contaminated by Ph+ cells, using predominantly HU as the mobilizing regimen. It is clear that higher numbers of Ph-negative cells can be obtained after mobilization of PBPC with ICE or Mini-Ice 33 than with HU regimen, 12,18 but near 5% of mortality rate related to the effects of intensive chemotherapy has been described. 14,16 PBPC mobilized with HU were clearly capable of sustained engraftment in our patients, and determined mainly cytogenetic and molecular cytogenetic responses in all of them during variable periods of time, in accordance with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Patients Eighty‐six patients, median age 42 years (20–67), with Hodgkin's disease (HD; n = 27), non‐Hodgkin's lymphoma (NHL; n = 28, mostly follicular n = 8, diffuse large B cell n = 5 or centrocytic/centroblastic lymphoma n = 4), multiple myeloma ( n = 19), chronic granulocytic leukaemia (CGL; n = 5), chronic lymphocytic leukaemia (CLL; n = 4) or breast cancer ( n = 3). Patients were mobilized with cyclophosphamide 2 g/m 2 , followed by 300 µg/d granulocyte colony‐stimulating factor (G‐CSF) from d +1, except for the CGL patients who were mobilized with a combination of hydroxyurea (average 3·5 g/m 2 for 7 d) and G‐CSF as above (Pratt et al , 1998) . CD34 selections were performed on nine patients (myeloma: CELL‐PRO n = 1, ISOLEX n = 1; lymphoma: ISOLEX n = 3; CLL ISOLEX n = 4, followed by CD19/CD23 depletion).…”
Section: Methodsmentioning
confidence: 99%
“…We read with interest the report of Pratt et al 1 concerning the use of autotransplantation using Ph-negative blood progenitor cells mobilized with hydroxyurea and G-CSF in chronic myeloid leukemia (CML) patients. The main conclusion of this study is that such a method provided a less toxic procedure for obtaining progenitor cells to support an intensive conditioning regimen.…”
mentioning
confidence: 89%